2017
DOI: 10.26905/jkdp.v21i1.1232
|View full text |Cite
|
Sign up to set email alerts
|

Dampak Profitabilitas, Aliran Kas Bebas, Dan Kesempatan Investasi Terhadap Pembayaran Dividen Perusahaan Perbankan

Abstract: This study aimed to identify and analyze the factors that affected paid dividend proxies by Dividend Payout Ratio (DPR) on the banking companies listed in Indonesia Stock Exchange (IDX). Multiple regression was a model of analysis that was used by the researchers to examine several variables which might affect the dividend payout ratio such as profitability, free cash flow, and investment opportunity set as independent variables, as well as firm size as a control variable. The samples in this study were 29 con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
9
1
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(30 citation statements)
references
References 6 publications
3
9
1
3
Order By: Relevance
“…In other words, ROA is a factor that companies use as a reference in making policies to pay dividends. This result is in line with the findings that the DPR significantly influenced ROA (Ahmad and 213 Wardani, 2014;Al-Kayed, 2017;Baker et al, 2019;Basuki and Kuswanto, 2016;Gean Karlos Purba, 2019;Mardiyati, 2014;Mubarok, 2016;Pradana and Sanjaya, 2017).…”
Section: Return On Assets Significantly Direct Effect On Dividend Pay-out Ratiosupporting
confidence: 89%
See 3 more Smart Citations
“…In other words, ROA is a factor that companies use as a reference in making policies to pay dividends. This result is in line with the findings that the DPR significantly influenced ROA (Ahmad and 213 Wardani, 2014;Al-Kayed, 2017;Baker et al, 2019;Basuki and Kuswanto, 2016;Gean Karlos Purba, 2019;Mardiyati, 2014;Mubarok, 2016;Pradana and Sanjaya, 2017).…”
Section: Return On Assets Significantly Direct Effect On Dividend Pay-out Ratiosupporting
confidence: 89%
“…The results of previous studies found ROA directly affected the DPR significantly (Ahmad and Wardani, 2014;Al-Kayed, 2017;Baker et al, 2019;Basuki and Kuswanto, 2016;Gean Karlos Purba, 2019;Mardiyati, 2014;Mubarok, 2016;Pradana and Sanjaya, 2017). When the value of ROA is greater, it will show the better performance of the company and the impact on the level of return on investment of the company.…”
Section: Retun On Assetsdirect Effect On Dividend Payout Ratiomentioning
confidence: 89%
See 2 more Smart Citations
“…Pada dasarnya profitabilitas memiliki kemampuan mengasilkan laba perusahaan, tetapi bila kita lihat kembali profitabilitas mempunyai peranan yang sangat penting dalam meningkatkan nilai perusahaan karena profitabilitas mampu mengukur laba yang didapatkan oleh perusahaan. Sedangkan menurut (Pradana & Sanjaya, 2017), menyatakan bahwa ada beberapa faktor yang mempengaruhi nilai perusahaan diantaranya: keputusan pendanaan, kebijakan dividen, keputusan investasi, pertumbuhan perusahaan, dan ukuran perusahaan.…”
Section: Landasan Teori Price To Book Valueunclassified